THE ROLE OF THE GENERAL PROLOGUE IN ESTABLISHING COMPOSITION - Suhrob Hasanov Shavkat ugli; So’poqova Mahfuza Furqat qizi; Shamsiddinov Bunyod (TADQIQOTLAR, 2026)
Annotation:  This  article  examines  the  role  of  the  General  Prologue  in establishing composition in Geoffrey Chaucer’s The Canterbury Tales. The General Prologue  serves  as  the  structural  and  thematic  foundation  of  the  entire  work, introducing the setting, the pilgrimage framework, and the diverse group of characters who  participate  in  the  storytelling  process.  It  plays  a  crucial  role  in  shaping  the narrative organization, connecting individual tales into a unified literary composition. Through  vivid  characterization,  social  representation,  and  detailed  description, Chaucer creates a complex artistic structure that reflects the social, cultural, and moral realities of medieval England.